Comparative study of analgesic effect of intrathecal bupivacaine and bupivacaine with fentanyl during and after cesarean delivery - Satyendra Uike; Shashibala Choudhary; Amit Jain (International Journal of Medical Research and Review, 2015)
Introduction: Neuraxial administration of opioids added to local anesthetics improves the quality of intraoperative analgesia and also provides postoperative pain relief for long duration. The aim of our study was to compare the analgesic effect of subarachnoid block with 10mg ,0.5% hyperbaric bupivacaine with combination of10mg , 0.5% hyperbaric bupivacaine and 12.5 µg fentanyl in parturient posted for elective caesarean section.Methods: All the parturient of ASA grade 1 and 2 were randomized allocated into two groups of 40 each. Group B received 10mg of 0.5% hyperbaric bupivacaine and group BF received 10mg 0.5% hyperbaric bupivacaine with12.5 µg fentanyl. Characteristics of sensory and motor blockade with hemodynamic parameters were observed, recorded intraoperative and postoperatively.Results: 10 mg of 0.5% bupivacaine with 12.5 µg fentanyl produces effective level of sensory blockade and less intensive motor blockade, maintains stable intraoperative hemodynamic parameters with decrease incidences of adverse effects like nausea and vomiting, shivering. The total duration of effective analgesia was significantly longer in fentanyl group. Pruritus was significant side effect in fentanyl group.Conclusion: Intrathecal fentanyl in dose of 12.5µg of fentanyl with bupivacaine for spinal anesthesia in caesarean section provides good intraoperative and significantly reduces the demand for postoperative analgesic with good maternal satisfaction and foetal well being.